Exploration of mosses in urban-bogor habitats: Species identification, diversity and uniformity - Ristanto, Rizhal Hendi; Rini, Daniar Setyo; Marthasari, Angela Diana; Safitri, Firdias Astia; Sulistiyanto, Tabitha Qotrunnada; Putri, Arlina Cahaya (STKIP Persada Khatulistiwa Sintang, 2024)
This research focuses on the exploration of moss in the Bogor urban habitat, to explore the identification of moss types, measuring the level of diversity, and assessing the level of uniformity in the context of the urban environment. Data collection at the research location was divided into 3 stations with different environmental parameters. The method used in this research was an exploratory survey using the belt transect technique. The sampling method is purposive sampling with the help of a quadratic plot. The results of this research found 20 moss species identified on the green belt of Jalan Pajajaran, Bogor with a diversity index for the three stations respectively, namely 2.45; 2.02; and 1.78 which is classified into the medium category, and the uniformity index for the three stations respectively is 0.835; 0.814; 0.811 which is classified as high. These results show that the moss found can live by adapting to environmental factors in urban areas such as fluctuating temperature, humidity, and light intensity.